(untitled) (Altre Modernità, 2017)
The proliferation of the so-called cultural studies, post-colonial studies and subordinates constitute a theoretical-methodological questioning of the modern ways of knowledge production. The "South" is these epistemologies’ enclave which, through the claim of fighting against the cognitive and social injustices, allowed the academics "other" the consolidation of their practices within the hierarchy of knowledge, due to the integration of new cognitive projects which, in turn, reaccomodate within the academy. The goal of this article is to elevate to the contradiction our intellectual work, which is as placed in the international division of knowledge’s contradictions as it is in the mutations and extensions of the modern paradigm.